P260 Potential Impact of the 2015 NICE Consultation Guideline for Tuberculosis on the number of children assessed and treated for TB infection and disease in the UK. (12th November 2015) - Turnbull, L; Bell, C; Child, F
Abstract : Background: NICE Tuberculosis (TB) guideline 2015 recommends all children, regardless of BCG status, with Mantoux ≥5 mm induration receive treatment for latent TB once active TB has been excluded. The 2011 version defines a positive Mantoux as ≥6 mm (no prior BCG) and ≥15 mm (prior BCG). NICE 2011 recommends screening of household contacts of all cases of TB compared with the 2015 guideline which recommends screening of contacts of pulmonary TB only. Objectives: To establish the impact of the change in NICE recommendations on the number of children assessed and treated for latent TB infection (LTBI) or TB disease in our department. Methods: We performed a retrospective analysis of all children. Results: 445 patients were referred, 75 with symptoms, 138 new entrants, 63 non-pulmonary contacts and 169 pulmonary contacts. Of those with symptoms, 5 had positive Mantoux (NICE 2011) compared with 18 (NICE 2015). In this group 0/75 were treated for LTBI and 7/75 for TB disease. Results of patients referred for contact tracing/new entrant screening are shown in Table 1 . Two contacts with LTBI and 1 with TB disease (all IGRA positive) would have been missed by the 2011 guideline but identified in 2015. Following NICE 2015 63 non-pulmonary contacts would not have been seen. None of these had LTBI or TB disease. Of the remaining 307 contacts/new entrants 47(15%) had a positive Mantoux of whom 11(4%) had LTBI and 4(1%) TB disease. Conclusion: 37% more children will be investigated and treated for TB infection/disease under the new NICE TB guideline. In a 12 month period in our clinic this represents 33 additional children with 1 extra case of TB disease and 2 cases of LTBI identified.